An optimal diet for planet and people - Kimani-Murage, Elizabeth; Gaupp, Franziska; Lal, Rattan; Hansson, Helena; Tang, Tang; Headey, Derek D.; Hirvonen, Kalle (Elsevier, 2021)
In 2019, the EAT-Lancet Commission proposed a planetary health diet (PHD)—optimal for the planet and its people. Yet concerns have arisen regarding its universality and potential tradeoffs and conflicts. This Voices asks: is a PHD realistic, where are the remaining knowledge gaps and opportunities, and where do we go from here?